Family and institutional narratives on barriers accessing schools in migrant families: A case study in Spain - Lubián, Carlos (Education Policy Analysis Archives, 2021)
This article explores the barriers of access in migrant families to primary education, starting from the school institution itself and exacerbated upon arrival. Based on qualitative methodology of interviews to directors of schools of high immigrant concentration and migrant families in Granada, we analyze the discourses on educational policies in charge of the offer and demand for school vacancies and system regulations conditioning school choice. We also discuss the influence of the schools themselves in their role as students’ hosts and on their increasing autonomy to manage schooling vacancies and provide specialized education –special mention to charter schools-. Results obtained show the “institutional barriers” faced by families because of their migratory status when choosing school for their children, at two levels: structural or systemic, due to access regulations that penalize these families to a greater degree; and in particular, as a consequence of discriminatory practices of certain schools towards them.